ANALISIS PENGARUH RASIO BOPO, LOAN TO DEPOSIT RATIO, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia) - Rizqi Nugraheni Utami (Journal Competency of Business, 2021)
The value of the company is one of the considerations of investors before deciding to provide funds to the company. This study aims to determine the effect of the ratio of Operating Expenses on Operating Income (BOPO), Loan to Deposit Ratio (LDR), and profitability on firm value. The population of this study are banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sample companies in this study amounted to 34 banking companies and the determination of the sample used purposive sampling technique. This study uses a quantitative approach. The data analysis technique used is multiple regression analysis which was previously tested with the classical assumption test. The data was processed using SPSS 25. The results of this study indicate that, (1) BOPO has a negative effect on firm value, this is indicated by a significant value of 0.005 which means it is smaller than = 0.05 with a coefficient value of -0.117. (2) LDR has a positive effect on firm value, this is indicated by a significant value of 0.003 which means it is smaller than = 0.05 with a coefficient value of 0.524. (3) profitability has a positive effect on firm value, this is indicated by a significant value of 0.014 which means it is smaller than = 0.05 with a coefficient value of 0.206.